STRESSED STATE CORRESPONDING TO THE FORMATION OF LARGE-SCALE BRITTLE FAILURE OF ROCKS - Rebetskii Yu.L. (My University, 2007)
Issue of relations between brittle failure and localized plastic flow, which are realized in the fault zones of the Earth’s crust, is one of the most important problems in geomechanics. New data on values of natural stresses in seismoactive regions allowed us to distinguish the regularities of their distribution, which correspond to the possibility of the appearance of large-scale brittle failure. It was found that areas of medium and low levels of confining pressure are the most hazardous regions in terms of a strong earthquake. Here, a small part of the released energy is consumed for negotiating friction forces. Therefore, brittle failure is more efficient. In the regions of high rock pressure, the dissipation of elastic energy is realized as creep along the fault or cataclastic flow due to a large number of weak earthquakes.